EFEKTIVITAS TERAPI PIJAT BAYI TERHADAP PERTUMBUHAN DAN PERKEMBANGAN BAYI USIA 6 BULAN DI KLINIK ASTER - Dewi Rubi Fitriani; Yayuk Sri Rahayu; Rina Dwi Anggraeni; Fitri Wulan; Mizrania Mizrania (Jurnal Kesehatan dan Kedokteran, 2025)
The first year of life is a critical period for infant growth and development. During this stage, optimal stimulation is essential to support physical growth, neurological maturation, and developmental achievements. Infant massage is recognized as a non-pharmacological intervention that may enhance growth and development through tactile stimulation, improved circulation, better sleep quality, and enhanced parent–infant interaction. This study aimed to determine the effectiveness of infant massage therapy on the growth and development of six-month-old infants at Aster Clinic. This study employed a quantitative approach using a quasi-experimental one-group pretest-posttest design. The study involved 20 infants aged six months who received infant massage therapy once a week for one month. Data were collected through measurements of body weight and developmental assessment scores before and after the intervention. Data analysis was performed using descriptive statistics and paired sample t-test with a significance level of 0.05. The results showed that the mean body weight increased from 6.36 kg before the intervention to 7.00 kg after the intervention. In addition, the mean developmental score increased from 12.3 to 17.4. Statistical analysis revealed significant differences in both growth and developmental outcomes before and after infant massage therapy (p < 0.001). These findings indicate that infant massage therapy effectively improves physical growth and developmental performance among six-month-old infants. The study highlights the potential of infant massage as a simple, safe, and cost-effective intervention to support early childhood growth and development. The originality of this research lies in the simultaneous evaluation of growth and developmental outcomes following infant massage therapy in six-month-old infants. The findings provide evidence to support the integration of infant massage into maternal and child health promotion programs.